A web architecture for an information system for Malaysian music - Ang, Minni Kim Huai; Ramani, Ashwani Kumar; Othman, Abu Talib (Masters of Library and Information Science Unit, Faculty of Computer Science and Information Technology, University of Malaya, 1998)
The design and development of a comprehensive web resource on Malaysian music involves the archiving of information from published and unpublished sources, based on a previously developed classification scheme. The data to be presented includes text data, audio samples, music sequences, still images, video data, and animated graphics. The web site architecture comprises two layers - the visible layer, determined by the subject architecture; and the underlying layer, or the application architecture, which is dependant to a certain extent on the visible layer, but does not mirror its structure completely. The development procedure starts with the data preparation, including the organization of the information content to be published, and the selection of specific data formats to be used. Software design issues include: objectives, system components, the subject architecture, and the application architecture. Coding and testing are also carried out. Site performance and access results indicate that the proposed web architecture is suitable for the delivery of information on Malaysian music over the World Wide Web (WWW).